Use of anastrozole for breast cancer prevention (IBIS-II): long-term results of a randomised controlled trial. Issue 10218 (11th January 2020) - Cuzick, Jack; Sestak, Ivana; Forbes, John F; Dowsett, Mitch; Cawthorn, Simon; Mansel, Robert E; Loibl, Sibylle; Bonanni, Bernardo; Evans, D Gareth; Howell, Anthony; ,
Summary: Background: Two large clinical trials have shown a reduced rate of breast cancer development in high-risk women in the initial 5 years of follow-up after use of aromatase inhibitors (MAP.3 and International Breast Cancer Intervention Study II [IBIS-II]). Here, we report blinded long-term follow-up results for the IBIS-II trial, which compared anastrozole with placebo, with the objective of determining the efficacy of anastrozole for preventing breast cancer (both invasive and ductal carcinoma in situ) in the post-treatment period. Methods: IBIS-II is an international, randomised, double-blind, placebo-controlled trial. Postmenopausal women at increased risk of developing breast cancer were recruited and were randomly assigned (1:1) to either anastrozole (1 mg per day, oral) or matching placebo daily for 5 years. After treatment completion, women were followed on a yearly basis to collect data on breast cancer incidence, death, other cancers, and major adverse events (cardiovascular events and fractures). The primary outcome was all breast cancer. Findings: 3864 women were recruited between Feb 2, 2003, and Jan 31, 2012. 1920 women were randomly assigned to 5 years anastrozole and 1944 to placebo. After a median follow-up of 131 months (IQR 105–156), a 49% reduction in breast cancer was observed for anastrozole (85 vs 165 cases, hazard ratio [HR] 0·51, 95% CI 0·39–0·66, p<0·0001). The reduction was larger in the first 5 years (35 vs 89, 0·39, 0·27–0·58, p<0·0001), but still significant after 5 years (50 vs 76 new cases, 0·64, 0·45–0·91, p=0·014), and not significantly different from the first 5 years (p=0·087). Invasive oestrogen receptor-positive breast cancer was reduced by 54% (HR 0·46, 95% CI 0·33–0·65, p<0·0001), with a continued significant effect in the period after treatment. A 59% reduction in ductal carcinoma in situ was observed (0·41, 0·22–0·79, p=0·0081), especially in participants known to be oestrogen receptor-positive (0·22, 0·78–0·65, p<0·0001). No significant difference in deaths was observed overall (69 vs 70, HR 0·96, 95% CI 0·69–1·34, p=0·82) or for breast cancer (two anastrozole vs three placebo). A significant decrease in non-breast cancers was observed for anastrozole (147 vs 200, odds ratio 0·72, 95% CI 0·57–0·91, p=0·0042), owing primarily to non-melanoma skin cancer. No excess of fractures or cardiovascular disease was observed. Interpretation: This analysis has identified a significant continuing reduction in breast cancer with anastrozole in the post-treatment follow-up period, with no evidence of new late side-effects. Further follow-up is needed to assess the effect on breast cancer mortality. Funding: Cancer Research UK, the National Health and Medical Research Council Australia, Breast Cancer Research Foundation, Sanofi Aventis, and AstraZeneca.